Inovasi Kampung Tematik di Kota Semarang, Pembangunan Kawasan Kumuh Berbasis Partisipasi dan Pemberdayaan Masyarakat (Studi Kasus: Kampung Sehat Ramah Anak) - Widiastuti, Rizka Nuri; Yuwono, Teguh (Journal of Politic and Government Studies, 2019)
This research is motivated by the emerge of Thematic Village Innovation in Semarang City. The aim is to raise potential while resolving problems that arise in the community. In order to improve community welfare, regional governments need to make changes in the form of efforts to overcome existing social problems and to develop the community.The method used in this study is a mixed method with qualitative and quantitative approaches with descriptive methods. The purpose of this study was to obtain data on participation in innovation and community empowerment in Kampung Sehat Ramah Anak, which is one of the Thematic Villages formed in 2016 which was once a slum area and whose children did not have positive activities. The study and analysis are based on literature studies and actual conditions and the tendency of community participation in innovation and empowerment in Kampung Sehat Ramah Anak. Study and analysis based on literature studies and the actual conditions and trends in community participation in innovation and empowerment in Kampung Sehat Ramah Anak.The results of this study show the innovation in the community, the characteristics of the community in the knowledge of innovation, participation in innovation planning, knowledge of the actors and programs provided and community participation in empowerment activities. Therefore, the importance of involving the community in each activity starts from the beginning of planning to evaluation. So that innovations made by the government can run smoothly and sustainably.Keywords: Innovation, Thematic Village, Participation, Community Empowerment